(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2010)
One of important steps in decaffeination process is steaming. The aim of steaming is to expand coffee beans porosity in order to obtain optimal condition for decaffeination process. Steaming can be done in single column reactor using saturated water vapour as media. The objective of this research is to study physical characteristics of coffee beans after steaming process using single column reactor. Material tested was Robusta coffee with 13—14% moisture content after dry processing. Reactor capacity is 6 kg dried coffee beans and 30 l water to produce water vapour. Dried coffee beans classified in 4 grades, i.e. diameter size (d) d>7,5 mm; 6,5<d³7,5 mm; 5,5<d£6,5 mm; and d£5,5 mm. Period of steaming process varied from 1 up to 3.5 hours. The result showed that the coffee beans expanded 8.6—9.5% in length, 12.2—13.3% in width, and 18.3—20.6% in thickness. Coffee bean volume increased 30—50%. Coffee bean moisture content increased f. Aritmatic diameter increased 8—13% while geometric diameter increased 9—18%. Sphericity not affected. Surface area increased 18—37%. True density increased 19—30% while bulk density was while. Porosity increased from 13—18% to 24—39% while coffee beans texture decreased from 323—384 g/1 mm to 212—225 g/1 mm. Color change increased from 14—20 to 38—40. The optimum steaming process was 3 hours. Key words : Coffee, steaming, single column reactor, decaffeination.